2016
DOI: 10.1111/ibi.12388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fragmentation and hybridization on geographical patterns of song variation in the endangered Yellow Cardinal Gubernatrix cristata

Abstract: The song learning process may lead to small‐scale geographical variation in vocalizations of oscine birds. This variation can be further enhanced by the effects of habitat fragmentation or hybridization. Populations of the endangered Yellow Cardinal Gubernatrix cristata are now patchily distributed in the southern South American thorny shrubland forests and are small as a consequence of the pressure exerted by increased habitat transformation and illegal trade. We study the Yellow Cardinal's vocalizations thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…The recent sightings published in this study confirm that Yellow Cardinal distribution is highly fragmented (Zelaya and Bertonatti 1995; Figure 1b). The three major occupied areas coincide with the management units previously suggested by population structure analyses (Domínguez et al 2016(Domínguez et al , 2017. The presence of cardinals in between these regions is scarce (Reales et al 2019).…”
Section: Current Distributionsupporting
confidence: 70%
See 2 more Smart Citations
“…The recent sightings published in this study confirm that Yellow Cardinal distribution is highly fragmented (Zelaya and Bertonatti 1995; Figure 1b). The three major occupied areas coincide with the management units previously suggested by population structure analyses (Domínguez et al 2016(Domínguez et al , 2017. The presence of cardinals in between these regions is scarce (Reales et al 2019).…”
Section: Current Distributionsupporting
confidence: 70%
“…Based on published records, Reales et al (2019) constructed a distribution map of the species and found a reduction in the original distribution. Previous work on genetic (Domínguez et al 2017) and song (Domínguez et al 2016) differentiation of isolated populations supported the existence of three management units (Moritz 1994) in Argentina. The geographical variation in vocalisations could enhance detection, especially when using playback.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Particularly in birds, song dialects are critical in attracting females, and male success is related to song recognition (Podos ). In this sense, it has been shown that the yellow cardinal's genetic MUs also exhibit different dialects (Domínguez et al ). Thus, incorporating genetic analysis into a management plan could help assigning the unknown origin of many confiscated cardinals kept in captivity and increasing their chances of survival.…”
Section: Discussionmentioning
confidence: 99%
“…This species was historically found throughout Uruguay, southern Brazil and the espinal region (thorny deciduous shrubland forests) of central Argentina (Ridgely and Tudor 2009, Domínguez et al 2015). However, for over a century, extensive poaching of male Yellow Cardinals for the illegal pet trade (Pessino and Tittarelli 2006) combined with the destruction of its habitat for agriculture and cattle pasture (Domínguez et al 2016) have severely affected this species. Yellow Cardinals are now very rare in Brazil; fewer than 300 individuals are believed to remain in Uruguay and the populations in Argentina are discontinuous and reduced in size (Domínguez et al 2015).…”
Section: Introductionmentioning
confidence: 99%